2022
DOI: 10.15625/2615-9783/16874
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface temperature trend analysis by Mann-Kendall test and sen’s slope estimator: a study of the Hai Phong coastal area (Vietnam) for the period 1995-2020

Abstract: Based on the Mann-Kendall test and Sen’s slope method, this study investigates the monthly, seasonal, and annual sea surface temperature (SST) trends in the coastal area of Hai Phong (West of Tonkin Gulf) based on the measurements at Hon Dau Station from 1995 to 2020. The results show a sea surface warming trend of 0.02°C/year for the period 1995-2020 (significant level α = 0.1) and of 0.093°C/year for the period 2008-2020 (significant level α = 0.05). The monthly SSTs in June and September increased by 0.027°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In this study, the magnitude and rate of change in the temperature (°C/year) and rainfall (mm/year) on the annual as well as on the seasonal scale over the study area were estimated using the Sen's slope estimator method. As mentioned earlier in the literature review section, this method has been applied in various studies in the past to determine the magnitude of trends in the meteorological time series data [28,31,36,42]. The statistics for the Sen's slope estimator method were computed using the following equations [27]:…”
Section: Sen's Slope Estimator Methodsmentioning
confidence: 99%
“…In this study, the magnitude and rate of change in the temperature (°C/year) and rainfall (mm/year) on the annual as well as on the seasonal scale over the study area were estimated using the Sen's slope estimator method. As mentioned earlier in the literature review section, this method has been applied in various studies in the past to determine the magnitude of trends in the meteorological time series data [28,31,36,42]. The statistics for the Sen's slope estimator method were computed using the following equations [27]:…”
Section: Sen's Slope Estimator Methodsmentioning
confidence: 99%
“…Some recent studies have also shown that the coastal area of Hai Phong is affected by climate change. Sea surface warming trend was +0.02 • C/year for the period 1995-2020 and of +0.093 • C/year for the period 2008-2020 [54]; the average annual rise of sea level was 7.78 mm/year over the periods 2002-2020 [50].…”
Section: Hai Phong Coastal Areamentioning
confidence: 99%
“…Recently, Ca [28] illustrated that the Bai Chay tide gauge sea level increased by 2.07 mm/year from 1961 to 2012. Some recent studies use Mann-Kendall, Sen's slop, and the Empirical mode decomposition methods (EMD) to calculate water level and temperature trends due to climate change at annual, seasonal, and monthly scales at the Hon Dau station as well as show the relationship between ENSO and these factors [37,38]. However, all research in Ha Long coastal area only calculated annual SLR and did not analyze the trend of SLR on monthly and seasonal scales.…”
Section: Figure 1 the Ha Long Coastal Area And The Ha Long Stationmentioning
confidence: 99%